PENGARUH PROFITABILITAS PERTUMBUHAN PENJUALAN DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2020 - 2022 - Ni Komang Ayu Trisnadewi; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2024)
Capital structure is a comparison between the composition of debt and own capital. Capital structure is very important to increase productivity and performance. The company's funding policy determines the capital structure that optimizes company value. An optimal capital structure, apart from providing high returns to shareholders, will also increase the competence of the company itself. This research aims to analyze and determine the influence of profitability, sales growth and business risk on the capital structure of mining sector companies listed on the Indonesia Stock Exchange. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2020 - 2022. The sample in this study was 57 companies determined based on purpose sampling. Based on the analysis carried out that there is outlier data, it is necessary to retest after the outlier data has been removed, the sample in this study is 31. The research method used in this research is multiple linear regression analysis. Based on the research results, it shows that profitability has a negative effect on capital structure, sales growth has no effect on capital structure and business risk has a positive effect on capital structure. It is hoped that further research can develop this research by using other variables which theoretically have an influence on capital structure